PENGARUH VARIASI PASSING DAN TARGET TERHADAP KETEPATAN PASSING MENGGUNAKAN KAKI BAGIAN DALAM PEMAIN SEPAK BOLA TIM SMPN 7 MUARO JAMBI - WIDIARSO WIDIARSO (Jurnal Tunas Pendidikan, 2020)
Football is one of the PJOK subject material which is then developed further in extracurricular activities and is used as a sport that is competed between schools, in football games there are basic passing techniques which, according to the writer's observation at SMPN 7 Muaro Jambi, are less noticed by the coaches, players who have been prepared to the school team is still not optimal. This is because the coaches have very few programs to train the passing accuracy of players, this is obtained from students' own statements that say they are bored with the training methods provided by the coach. This study aims to determine the effect of variations in passing and targets on passing accuracy using the inner legs of the soccer player Muaro Jambi Junior High School 7. The method used in this research is quantitative experiment, which is a study in which the researcher gives treatment after the initial test is taken and the final test will be taken again after being treated, then it will be seen whether the independent variables play a role in the onset of symptoms. From the statistical test, the average initial passing test for the accuracy of passing soccer players for MPN 7 MPN junior high school team was 9, after being given an average treatment, the final passing accuracy increased to 17, thereby increasing the initial test. The conclusion of this thesis is the t test statistic test is greater than t table or 20.69> 1.729, so there is an influence of passing and Target practice variations on the passing accuracy of soccer players at Muaro Jambi SMPN 7 team.